PERCUTANEOUS NEPHROLITHOTOMY LITHOTRIPSY: THE ROLE OF BALLISTIC AND ULTRASONIC ENERGY (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
The medical industry is in continuous search for improved techniques aimed at helping medical professionals treat urinary stones more effectively. When it comes to stones disintegration, several sources of energy are available, but two of them imposed as being the most effective: ballistic and ultrasonic. The aim of our paper is to review the literature in search for current evidence regarding the usage and limits of these sources of energy. We reviewed the latest papers on currently used devices for PCNL lithotripsy. We used as search terms “lithotripsy”, “ballistic lithotripsy” and “ultrasonic lithotripsy”, “combined lithotripsy”. Only original papers were considered eligible.
Keywords: Ultrasonic lithotripsy; Ballistic lithotripsy; Percutaneous nephrolithotomy (PCNL)